Comparison of Prevalence and Associated Factors of Multisystem Health Symptoms Among Workers in the Gas Station Area, Thailand - Polyong, Chan Pattama; Thetkathuek, Anamai (Kesmas, 2023)
This cross-sectional study aimed to compare the prevalence of multisystem health symptoms (MHS) of workers in gas station areas before and after their employment and examine the factors affecting the MHS of workers. Data were collected by an interview questionnaire from 200 workers inside and outside refueling areas at eight gas stations in Rayong Province, Thailand. This study found that employees had a statistically significant increase in the prevalence of current MHS in comparison to before starting work (p-value<0.05), with 31.5%. Working overtime for more than 6 hours per week led to respiratory symptoms (OR = 2.63, 95% CI = 1.14–6.07) and psychological symptoms (OR = 2.69, 95% CI = 1.12–6.49). Wearing respiratory protective equipment for less than three hours affected ear/throat/nose systems (OR = 4.26, 95% CI = 1.43–12.65). Petrol refueling resulted in liver (OR = 2.32, 95% CI = 1.4–12.65) and eye symptoms (OR = 2.57, 95% CI = 1.10–5.39). Therefore, gas station owners should set up enclosed rooms to reduce the duration of fuel exposure, and workers should wear personal protective equipment when refueling or near the dispenser.